Hygiene of the external auditory canal - K. A. Nikitin (Медицинский совет, 2013)
As is well known, 4 to 10% of patients seeking ENT care have cerumen impaction [4, 5]. Cerumen is a major cause of hearing loss in more than 5.5 million people in Russia annually. The main factors contributing to cerumen impaction are active use of cotton wool sticks, moisture in the ear, prolonged use of headphones, excessive hair growth in the ear canal and use of hearing aids.